Pengaruh Habitat Sekitar Lahan Persawahan dan Umur Tanaman Padi terhadap Keanekaragaman Hymenoptera Parasitika - Nina Herlina; Akhmad Rizali; Moerfiah Moerfiah; Bandung Sahari; Damayanti Buchori (Jurnal Entomologi Indonesia, 2011)
As the largest group of biological control agents, Parasitic Hymenoptera play important role in controlling pest outbreak in agricultural habitat. Unfortunately, there is lack of information about how these parasitoids occur in agricultural habitat related to condition of surrounding habitat and phenology of crop plant. The objective of this research was to study the effect of rice field surrounding habitat and age of rice plant on the diversity of Parasitic Hymenoptera. Research area was located in Carang Pulang Village, Dramaga, Bogor. We selected four blocks which represented different of habitat condition and age of rice plant. Each block was set six yellow pan traps (with minimum distance 20 meter) and one malaise trap. Sampling of insects were conducted weekly from 6 to 12 week after planting. From this research, we collected 1,833 individual of Hymenoptera (without ants) belong to 9 superfamilies, 23 families, and 216 species. Parasitic Hymenoptera was more abundant (96%) and species rich (84%) than Aculeata. Rice field surrounding habitat (block) and age of rice field significantly affect the diversity of Parasitic Hymenoptera. We found positively correlation between age of rice plant and species richness of Parasitic Hymenoptera.